Reflections on the teaching of philosophy in Brazil: a critical exercise - Prates, Letícia Pedrassa (Universidade Estadual de Campinas, 2020)
The aim of this article is to investigate, according to the studies of Philosophy of Education, certain practices of teaching Philosophy in the field of Basic Education. In this perspective, two specific teaching practices are analyzed: the first one, based on a historical approach to Philosophy; the second one, alluding to a supposed departure from traditionalist pedagogical practices, supported by a vague notion of debating. Considering the problematization of both practices, we emphasize the need to promote the teaching of Philosophy towards a strong connection between past and contemporary times.